A young male patient with cardiomyopathy associated with human immunodeficiency virus infection in the era of highly active antiretroviral therapy - Fathurohim, Zainal; Martini, Heny (Universitas Brawijaya, 2024)
Background: Cardiomyopathy in young people, especially those associated with HIV infection, has been reduced since the era of Highly Active Antiretroviral Therapy (HAART). In the era of post-HAART, manifestations of human immunodeficiency virus (HIV)-associated cardiomyopathy with impaired left ventricular (LV) systolic function are approximately about 1-3% of HIV-infected people. In this case, we presented how to diagnose and appropriately manage such a patient.Case Illustration: A 27-year-old male patient who works as a health worker came to the emergency room with complaints of shortness of breath; it worsened in the last 2 weeks. He got vital signs: blood pressure 97/60 mmHg, heart rate 118 bpm, respiratory rate 23 tpm, and oxygen saturation 99 % with oxygen supplementation of 8 lpm. Risk factors in patients such as smoking, family history, hypertension, diabetes mellitus, and dyslipidemia were denied. He was diagnosed with HIV on (antiretroviral therapy) ART 3 years ago with risk factors for free sex without protection. The last CD4 value was 796 cells/ul (normal value 637 – 1485). The echocardiography showed all chamber dilatation, global hypokinetic, and a significant decrease in LV systolic function (LVEF 16%). Laboratory examination showed an increase of N-terminal prohormone of brain natriuretic peptide (NT-proBNP) into 6824 pg/mL (normal value <85.8). It was then treated by optimizing HF therapy continue HIV therapy.Conclusion: In HIV patients who have fallen into heart failure, a proper diagnosis using relevant tools could be a reference for clinicians to make the right decision. Prompt treatment combination of optimal HF therapy and HIV therapy are becoming the keys to the treatment.